World Council of Churches (WCC) Should Raise the Visibility of Ukrainian Orthodox at the World Assembly (Karlsruhe, Sept. 2022): Interview with Professor Katharina Kunter - Kunter, Katharina (Occasional papers on religion in Eastern Europe, 2022)
"I think, that the WCC Executive Committee meeting in June, will not be able to expel the ROC. In my view, that leaves only one reasonable solution, in order as ecumenical assembly to remain credible. The Ukraine must be made visible as Church in Karlsruhe. That means, the WCC (or the EKD) must immediately and officially approach the autocephalous Orthodox Church of Ukraine (OKU). They should offer it a "fast-track-membership in the WCC and offer it a visual public forum at the full assembly. The OKU is now already the largest Orthodox Church in the Ukraine, with nearly 50% of all Orthodox believers. Currently, while the war rages, daily parishes and monasteries are deciding to leave the UOK and to transfer to the OKU. One should, for church political and ecumenical reasons, openly and constructively support a union of OKU and UOK. How the ROC reacts to the situation, remains to be seen. In any case the WCC would have opened up a diplomatic space to negotiate and need not react under pressure. Even if the ROC were to leave WCC membership, it would not be the WCC that had expelled them." Translated by Walter Sawatsky